Альфа-бөлшектердің көміртегі ядроларында шашырауы кезіндегі зат алмасу процестері : Альфа-бөлшектердің көміртегі ядроларында шашырауы кезіндегі зат алмасу процестері - Тулешов, Нұрдәулет (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
Abstract This article provides a comprehensive analysis of the mass–energy exchange processes and nuclear interactions occurring during the scattering of alpha particles by carbon nuclei. The study examines the penetration mechanism of alpha particles into the nucleus, the changes in their energy, and the specific features of elastic and inelastic scattering processes. In particular, the work describes in detail the modifications in the level structure of the carbon nucleus resulting from collisions with alpha particles, the formation of excited states, and the redistribution of energy within the nucleus. The article discusses the theoretical foundations of Rutherford scattering, the Coulomb barrier, quantum-mechanical tunneling phenomena, and the characteristics of interactions determined by the nature of nuclear forces. The role of experimental methods-such as particle detection detectors, scattering angle measurement techniques, and spectroscopic energy analysis-is also highlighted. The research findings demonstrate the significance of alpha-particle interactions with carbon nuclei for understanding nuclear structure physics. These processes play a crucial role in clarifying nuclear reaction mechanisms, investigating the properties of light nuclei, and improving applied studies in the fields of nuclear energy, medicine, and materials science. Keywords: alpha particle, carbon nucleus, scattering, nuclear reaction, elastic and inelastic collision, nuclear excitation levels, nuclear forces, energy transfer.